Genetic variants of the lipoprotein lipase gene and myocardial infarction in the Central Valley of Costa Rica - Yang, Yadong (2004)
To assess common variants of the LPL gene that could influence susceptibility to myocardial infarction (MI), we assessed three functional single-nucleotide polymorphisms (SNPs), D9N, N291S, and S447X, in 1,321 survivors of a first acute MI and 1,321 population-based controls, matched for age, gender, and area of residence, all living in the Central Valley of Costa Rica. Conditional logistic regression was used to estimate odds ratio (OR) and 95% confidence interval (CI). The frequency of the X447 mutant allele was significantly lower in cases than in controls (6.2% vs. 7.6%; P < 0.01), whereas no association with MI was found for D9N or N291S. The OR (95% CI) for carriers vs. noncarriers of the X447 allele was 0.80 (0.63–1.01); when considering the haplotype that contained X447 and normal alleles of D9N and N291S, the OR (95% CI) was 0.66 (0.48–0.91). Twelve other SNPs were assessed in a subgroup of the population, of which the four functional SNPs were found to be monomorphic, and no correlation with MI was observed for the other eight neutral SNPs. The X447 mutant allele of the LPL gene may protect from MI risk, although this effect is small.